2013
DOI: 10.1177/0284185113475917
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of postoperative main portal vein and superior mesenteric vein thrombosis with balloon angioplasty and/or stent placement

Abstract: Balloon angioplasty and/or stent placement without thrombolysis or thrombectomy may be a safe and effective treatment modality for postoperative main portal vein and superior mesenteric vein thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 27 publications
0
36
0
1
Order By: Relevance
“…PVT is a common complication in patients waiting for a LT with a prevalence ranging from 6% to 12% of patients . Its presence can make LT more difficult, especially with higher grades of PVT where elaborate reconstruction techniques to restore portal flow may be necessary .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PVT is a common complication in patients waiting for a LT with a prevalence ranging from 6% to 12% of patients . Its presence can make LT more difficult, especially with higher grades of PVT where elaborate reconstruction techniques to restore portal flow may be necessary .…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous transhepatic balloon angioplasty is a technique that has been used to treat PV thrombosis for a long time by interventional radiologists and is considered to be safe and effective . Usually, it is performed postoperatively when a CT scan shows a PVT with or without narrowing of the PV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors reported successful stenting of anastomotic portal vein stenosis after liver transplantation (6)(7)(8)and portal vein stenosis in non-transplant patients (4,(9)(10)(11), but far less is known about stenting in patients with isolated SMV stenosis. Similar to portal vein stenosis, isolated SMV stenosis can lead to severe venous stasis with refractory ascites, gastrointestinal bleeding and even bowel infarction (1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of flexible self-expanding nitinol stents with a small profile represents a possible minimally invasive alternative to open surgery.While percutaneous stenting of symptomatic benign and malignantportal vein stenosis has been reported in larger studies (4,(6)(7)(8)(9)(10)(11), very limited data exists regarding stenting of symptomatic SMV stenosis.Until now only 1 case series(1)and a few case reports (2,3)have been published with good results for SMV stenting.…”
Section: Introductionmentioning
confidence: 99%